What do translators do? seven popular myths debunked - Bell, Roger T. (Journal of Modern Languages, 2017)
Before translation can take its place as a fully accepted and legitimate area of academic investigation and translators can take their rightful place alongside other communication professionals, consensus must be reached on the definition of, at least, such key terms as translator, translation, interpreter, interpretation. interpreting and some attempt must be made to clear away some of the confusion which surrounds them. That is the key aim of this paper.